Pembinaan Agama Islam Sebagai Upaya Pencegahan Tindak Pidana Berkelanjutan Bagi Narapidana Kasus Narkoba di Lembaga Pemasyarakatan Kelas II B Kabupaten Mimika - Budi Utomo; Neti S; Mohammad Ali Mahmudi; Muh. Abdul Mukti; Zaidir (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study is motivated by the high recidivism rate among narcotics inmates and the need for a contextual Islamic religious rehabilitation approach at Class II B Correctional Facility in Mimika. The research aims to describe the implementation of Islamic religious guidance as a continuous crime prevention effort, including its supporting and constraining factors. Using a qualitative descriptive method, data were collected through semi-structured interviews, participative observation, and documentation. The population included narcotics inmates, religious instructors, the prison chief, and spiritual supervisors; purposive sampling selected seven key informants. Data analysis employed Miles and Huberman’s interactive model. Results reveal that religious guidance is effectively implemented through disciplined five daily prayers, regular recitations, and Quranic literacy practices, supported by strong collaboration and inmate engagement. The conclusion emphasizes the significance of Islamic religious rehabilitation in spiritual recovery but highlights the need for enhanced facilities, human resources, and individualized approaches to address inmates’ diverse backgrounds. Practically, the study recommends multi-stakeholder synergy to reduce recidivism rates.